The effects of three different type of exercises on aerobic and anaerobic power - Gorucu Alpaslan; Tokay Bekır; Badau Adela (Physical Education of Students)
Purpose: The study was conducted with the aim of investigating the effects of three different types of exercise: bicycling, plyometric and weight on aerobic and anaerobic power. Material: Sample size 30 students recreational athletes aged 23,19 years. The athletes were divided into 3 groups of 10 subjects (bicycle, plyometric, weight). The program for 6 weeks included: 3 different exercises planned for 30 minute/3 days/week. Body weight, vertical jump and 20-meter shuttle running tests were measured for each group. Statistical analysis was performed by SPSS21.0: arithmetic averages and standard deviations; the Kruskal-Wallis H test was used to determine the differences between the groups; the Mann-Whitney U test was used to determine the group which result in the difference among the groups; Wilcoxon 's t test was used to determine pretest posttest differences within the groups. Results: As a result of the research, it was determined that the increase in the aerobic power levels of the bicycle and plyometric groups was significant (p0.05). Conclusions: The different exercises practiced by all three groups significantly increased anaerobic power levels. When the aerobic and anaerobic power values of the three groups in each study were examined, it was found that only the increase of weight and plyometric groups was high level in favor of the weight group in terms of posttest aerobic power.